The undermining of Twyla and Frank - Bannen, Megan (Undertaking of Hart and Mercy, 2024)
"The entire town of Eternity was shocked when widowed, middle-aged Twyla Banneker partnered up with her neighbor and best friend, Frank Ellis, to join the Tanrian Marshals. Even her own children seemed appalled, save her youngest daughter Hope. Eight years later, Hope is off at medical school with the support of her mother's income, and Twyla and Frank are still patrolling Tanria, the former prison of the Old Gods. It's a mostly uneventful occupation since Marshal Hart took care of the infestation of the undead, but one Twyla refused to relinquish partly because her son Wade seems to expect that will leave her open to be a full time nanny for his children. But when Twyla and Hart discover the body of one of their fellow Marshals, covered in what looks like liquid glitter and near a footprint that can only be described as dragon-sized, the job suddenly becomes a lot more interesting. Everyone knows the existence of dragons in Tanria is nothing but a myth...until evidence to the contrary quite literally lands in Frank's hands in the form of a dragon egg. Quill, a handsome dracologist is called in from the university to help them investigate, and for the first time since her husband died, Twyla finds herself the flattering focus of an appropriately-aged man's attraction. Why on earth that should bother Frank, she doesn't know--but her longtime partner sure doesn't seem to care for Quill. As Twyla and Frank's investigation becomes more complicated, so does their easy friendship. And Twyla starts to realize that her true soul mate might just be the person who has lived next door all along.."--